Strength gain monitoring and construction quality evaluation on non-dispersible underwater concrete using PZT sensors. (7th March 2022) - Wang, Juan; Jiang, Shaofei; Cui, Erjiang; Yang, Wenjun; Yang, Zhengxian
Graphical abstract: Highlights: An evaluation method was proposed to assess the construction quality of UWC. The admixtures have an effect on early-age hydration of the UWC. The hydration of UWC can be divided into fluid, plasticized, and hardened stages. The prediction model makes it feasible to obtain the strength of practical structures. Abstract: Owing to the undrained construction, not only the admixtures but also the hardening process is believed to have a significant effect on the final strength of non-dispersible underwater concrete (UWC). To ensure the stability and workability of UWC, this paper defined the hydration stages of UWC by conducting an early-age hydration monitoring experiment based on PZT (Piezoceramic Lead-Zirconate-Titanate) sensors and an isothermal calorimetry experiment. Additionally, a 90-day strength gain monitoring experiment and a compressive strength experiment were also carried out to establish a semi-empirical strength prediction model, which can be utilized to assess the real strength of UWC by substituting the monitoring data from practical structures. With practical application in a corroded bridge pier strengthened by prefabricated Basalt FRP (BFRP) shell and UWC, the strength prediction model presents a high accuracy on the prediction of hardening strength of UWC, and all the indices of the practical bridge pier strengthened by BFRP and UWC meet with the design codes. This indicates that the strength monitoring approach and construction quality evaluation method can apply to practical underwater structures.